Effects of Preconditioning on RBC Deformability in Critically Ill Patients. (29th September 2022) - Moreau, Anthony; Zouaoui Boudjeltia, Karim; Biston, Patrick; Piagnerelli, Michael
Abstract : OBJECTIVES: RBCs from critically ill patients have depressed deformability, especially in sepsis. Prolonged exposure of RBCs from healthy volunteers to physiologic shear stress (the preconditioning technique) has been associated with improved deformability, but the effect of preconditioning on RBCs from critically ill patients with or without sepsis has never been studied. DESIGN: Prospective study. SETTING: A 32-bed medico-surgical ICU and a university-affiliated cell biology laboratory. SUBJECTS: RBCs from 26 healthy volunteers and 40 critically ill patients (20 with and 20 without sepsis). INTERVENTIONS: RBC deformability was measured using the elongation index (EI) with an ektacytometer, at shear stress levels ranging from 0.3 to 50 Pa. To assess the effects of preconditioning in the three groups, we measured EI after first applying a shear stress of 5 Pa for 300 seconds. To study the potential mechanisms involved in preconditioning, we looked at deformability after incubation of an RBC solution from the healthy volunteers with glutaraldehyde, a membrane-stabilizing protein, and neuraminidase, an enzyme that releases membrane sialic acid. MEASUREMENTS AND MAIN RESULTS: Baseline RBC deformability was significantly depressed in the septic patients compared with the volunteers at all shear stress levels greater than or equal to 4.89 Pa. Preconditioning improved deformability only in the volunteers (at shear stress levels of 0.48 and 0.76 Pa). Among the critically ill patients, preconditioning worsened RBC deformability at higher shear stress levels. After incubation (with glutaraldehyde or neuraminidase) of RBCs from five volunteers in whom preconditioning had significantly improved deformability, the positive effect of preconditioning was lost with glutaraldehyde. CONCLUSIONS: RBC deformability is depressed in septic patients. There was a deleterious effect of preconditioning on RBC deformability in septic patients, unlike the positive effect on RBCs from healthy volunteers. The effect of preconditioning may be associated with elasticity of the cell membrane.